The Influence of External Factors in Improving the Motivation of Arabic Language Learning of Arabic Language Education Students of UINSI Samarinda - Safira Aulia; Munirul Abidin; Farah Mardhiyyah binti Ab Razak (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2025)
In Arabic language learning at UINSI Samarinda, there are various obstacles. The researcher found that external factors influence students’ success in understanding lecture material. These factors include students’ Arabic education background, non-pesantren students, lack of daily use of Arabic vocabulary, and low learning motivation. The external factors studied are divided into two categories: social environmental factors (characteristics, family, and friends) and non-social environmental factors (geography and weather). The sample consisted of 21 eighth-semester students from the Arabic Education Program for the 2024/2025. The research method used simple quantitative linear regression with data collected through questionnaires and analyzed using IBM SPSS version 27.0. The t-test results showed a calculated t-value of 7.575, which is greater than the table value of 1.721, indicating a significant effect. The correlation coefficient (R) is 0.352, and the coefficient of determination (R²) is 0.124, meaning external factors contribute 12.4% to students’ learning motivation. In conclusion, there is a positive and significant influence of external factors on the motivation to learn Arabic among students at UINSI Samarinda. Therefore, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected.